Organizational Citizenship Behavior among Teachers: The Role of Organizational Pride and Organizational Justice - Fadhilah, Fathin; Izzati, Umi Anugerah; Mulyana, Olievia Prabandini; Isa, Khairunesa (Indonesian Psychological Research, 2026)
T Organizational Citizenship Behavior (OCB) is a crucial factor in the success of organizations, particularly educational institutions. This study aims to determine the role of organizational pride and organizational justice on organizational citizenship behavior among teachers. The present study used a quantitative research method with a correlational design. Participants of this study were teachers at the "X" Foundation, selected using proportionate stratified random sampling. Data collection was performed using three psychological questionnaires developed based on the theoretical concepts of each variable, namely Gouthier & Rhein's (2011) theory for organizational pride, Colquitt's (2001) theory for organizational justice, and Organ et al.'s (2006) theory for organizational citizenship behavior. The results showed that organizational pride had a significant positive relationship with organizational citizenship behavior. Organizational justice also had a significant positive relationship with organizational citizenship behavior. Simultaneously, both independent variables played a significant role in predicting organizational citizenship behavior. This study indicates that feelings of pride and positive perceptions of justice will motivate the emergence of volunteer work behavior among teachers.